Correlation of Serum Immunoglobulin-E Level with Relapsing Idiopathic Nephrotic Syndrome in Children - Syed Awais Haider Kazmi; Qudrat Ullah Malik; Bilal Akhlaq; Hafsa Arshad; Zohaib Akhter; Umair Anees (Medical Journal of South Punjab, 2025)
Objective: To correlate the relationship between the level of serum immunoglobulin-E in relapsing idiopathic nephrotic syndromeMethodology: We conducted this case-control study on 50 paediatric patients of both genders suffering from idiopathic nephrotic syndrome, who were aged between 2 and 12 years. Potential participants with a past history of urinary tract infections, non-nephrotic proteinuria, congenital nephrotic syndrome, secondary nephrotic syndrome, nephritic syndrome, and anatomical renal disorders were excluded. Patients were tested for serum Immunoglobulin E level.Results: Among the 50 participants, 29 (58.0%) were males, and 21 (42.0%) were females. 27 (54.0%) reported atopy in family. The mean age of the participants was 8.42 ± 2.81 years. The mean serum urea was 5.03 ± 1.33 mmol/L, and serum creatinine levels were 59.24 ± 11.47 µmol/L. The serum IgE levels were negatively correlated (r = -0.736, p